A balancing act: using small molecules for therapeutic intervention of the p53 pathway in cancer. (1st September 2020) - Miller, Jessica J.; Gaiddon, Christian; Storr, Tim
Abstract : Small molecules targeting various aspects of the p53 protein pathway have shown significant promise in the treatment of a number of cancer types. Abstract : Referred to as the "guardian of the genome", p53 is the most frequently mutated protein in cancer and almost all cancers exhibit malfunction along the p53 pathway. As an overexpressed and tumour-specific target, the past two decades have seen considerable dedication to the development of small molecules that aim to restore wild-type function in mutant p53. In this review we collect and communicate the chemical principles involved in small molecule drug design for misfolded proteins in anticancer therapy. While this approach has met with significant challenges including off-target mechanisms that induce cytotoxicity independent of p53 status, major technological advancements in gene sequencing capability and a shift towards personalized medicine holds significant promise for p53 reactivating compounds and could have widespread benefits for the field of cancer therapy.